Fungal biomass and ectomycorrhizal community assessment of phosphorus responsive Pinus taeda plantations - Hackman, Jacob; Woodley, Alex; Carter, David; Strahm, Brian; Averill, Collin; Vilgalys, Rytas; Garcia, Kevin; Cook, Rachel (Frontiers in Fungal Biology, 2024)
Ectomycorrhizal fungi and non-ectomycorrhizal fungi are responsive to changes in environmental and nutrient availabilities. Although many species of ectomycorrhizas are known to enhance the uptake of phosphorus and other nutrients for Pinus taeda, it is not understood how to optimize these communities to have tangible effects on plantation silviculture and P use efficiency. The first step of this process is the identification of native fungi present in the system that are associated with P. taeda and influence P uptake efficiency. We used sand-filled mesh bags baited with finely ground apatite to sample ectomycorrhizal and non-ectomycorrhizal fungi associated with the rhizosphere of P-responsive P. taeda under several field conditions. Mesh bags were assessed for biomass accumulation over three years using a single three-month burial period pre-harvest and three six-month burial periods post-planting. Amplicon sequencing assessed ectomycorrhizal and non-ectomycorrhizal communities between phosphorus treatments, sites, mesh bags, and the rhizosphere of actively growing P. taeda in the field. We found biomass accumulation within the mesh bags was inversely related to increasing phosphorus fertilization (carryover) rates from pre-harvest to post-planting. Up to 25% increases in total biomass within the bags were observed for bags baited with P. Taxonomic richness was highest in Alfisol soils treated with phosphorus from the previous rotation and lowest in the Spodosol regardless of phosphorus treatment.